2012
DOI: 10.1016/j.ophtha.2011.09.044
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Macular Degeneration and Incident Cardiovascular Disease: The Multi-Ethnic Study of Atherosclerosis

Abstract: Objective To determine whether age-related macular degeneration (AMD) is a risk indicator for coronary heart disease (CHD) and cardiovascular disease (CVD) events independent of other known risk factors in a multi-ethnic cohort. Design Population-based prospective cohort study. Participants A diverse population sample of 6233 men and women aged 45–84 without known CVD from the Multi-Ethnic Study of Atherosclerosis (MESA). Methods Participants in the MESA had retinal photographs taken between 2002 and 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…However, in the Cardiovascular Health Study [122] comprised of a cohort of white Americans and African Americans, early AMD but not late AMD was associated with an increased risk of CHD. The baseline presence of AMD did not predict occurrence of CHD or CVD in the Multi-Ethnic Study of Atherosclerosis (MESA, [123]) full population, but late AMD did associate with both CVD and CHD in a subgroup comprised of older (65+) white participants. In a meta-analysis published in 2014 of eight prospective and five retrospective studies, Wu et al [124] reported that patients with early AMD had an increased risk for CVD and for CHD.…”
Section: Epidemiology Of Cardiovascular Health and Amdmentioning
confidence: 99%
“…However, in the Cardiovascular Health Study [122] comprised of a cohort of white Americans and African Americans, early AMD but not late AMD was associated with an increased risk of CHD. The baseline presence of AMD did not predict occurrence of CHD or CVD in the Multi-Ethnic Study of Atherosclerosis (MESA, [123]) full population, but late AMD did associate with both CVD and CHD in a subgroup comprised of older (65+) white participants. In a meta-analysis published in 2014 of eight prospective and five retrospective studies, Wu et al [124] reported that patients with early AMD had an increased risk for CVD and for CHD.…”
Section: Epidemiology Of Cardiovascular Health and Amdmentioning
confidence: 99%
“…Stroke risk has been found to be associated with AMD in a court of patients from (52). However, an association between AMD and Coronary atherosclerotic heart disease (CHD) or Classical cardiovascular disease (CVD), in people without known risk factors of CVD, has failed to be found (53). Moreover, a novel study performed a meta-regression analysis seeking for an association with incident stroke but no association has been found (54).…”
Section: Risk Factors Protective Agents and Associated Conditionsmentioning
confidence: 99%
“…[1][2][3][4] AMD becomes clinically evident typically after 50 years of age, 5 and is classified based upon disease severity. 6 Early AMD is characterized by the presence of drusen and pigmentary abnormalities in the retinal pigment epithelium (RPE) and late AMD is characterized by degenerative changes in the RPE, Bruch's membrane, and choriocapillaris, resulting in geographic atrophy and/or neovascular AMD.…”
Section: Introductionmentioning
confidence: 99%
“…10 The disease is related to well-known risk factors, such as cigarette smoking, elevated serum cholesterol levels, and hypertension, that are shared with atherosclerosis and consequently with increased risk of cardiovascular disease (CVD). 1,6,11 Genetic studies have reported similar susceptibility genes for CVD and AMD, such as complement factor H loci. 9,12,13 Therefore, a modification in atherosclerotic changes with lipid-lowering medications may exert a preventive effect in AMD development by prevention of lipid deposits at the level of Bruch's membrane.…”
Section: Introductionmentioning
confidence: 99%